2-D physical model experimental study of ethyl acetate and steam co-injection for in-situ bitumen recovery. (1st April 2020) - Zirahi, Ali; Sadeghi Yamchi, Hassan; Haddadnia, Ali; Zirrahi, Mohsen; Hassanzadeh, Hassan; Abedi, Jalal
Abstract: In this work, we evaluate ethyl acetate (EA) as a solvent for bitumen recovery using a 2-D sand-pack physical model for the first time. EA was considered for co-injection with steam due to the promising results obtained from our recent experimental phase behavior and reservoir simulation studies. Two experiments were conducted by co-injection of 10 and 20 vol% of EA with steam to evaluate expanding solvent steam assisted gravity drainage (ES-SAGD). An experiment was also conducted for the steam assisted gravity drainage (SAGD) as a reference case. The results showed that co-injection of EA increases the bitumen rate. Both ES-SAGD experiments showed a higher production rate compared to SAGD and the superiority of ES-SAGD. The results of 10 and 20 vol% EA co-injection revealed ~65% and ~75% bitumen recovery, respectively, compared to 50% in the case of the SAGD experiment. Co-injection of EA with steam also decreased the cumulative steam-oil-ratio (cSOR), which is desirable in bitumen recovery processes. ES-SAGD experiments reduced the cSOR by 1.5 to 2.5 units, which is 20 to 32% lower than SAGD. This reduction in cSOR results in significant energy savings and lower greenhouse gas emission intensity. The cumulative energy-oil-ratio was also measured, and the results showed that co-injection of EA decreases the energy-oil-ratio by 17–22% compared to SAGD. Moreover, it was observed that implementation of EA significantly reduces the water-oil emulsion stability, which is favorable in oil/water separation and treatments of the produced water.